Empowering school citizens in behavior clean and healthy life through school health business - Hutagalung, Haflin Soraya; Amelia, Sri; Panggabean, Merina; Yosi, Ariyati; Balatif, Ridwan (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
One of the most problematic things faced by Indonesians is health issue, especially for school-age children. The cases which is occurred are behavioural disorder, the development of physiological disorder, learning disabilities, and general health problem, occur frequently in children. School Public Health is a place to promote Healthy and Clean Living Behaviour for school-age children. The community service team which consists of lecturer from Medical Faculty of Universitas Sumatera Utara do counseling and training activity in Susuk Village, Tiganderket sub-district, Karo disctrict. This activity was followed by 72 students, consisting of 18 students from grade 4, 33 students from grade 5, and 21 students from grade 6. Besides counseling and training activity, students was given a questionnaire form to measure their knowledge. From the answer of questionnaire, it was obtained that the respondent having good knowledge is 53 students (73,6%), 23,6% having moderate knowledge, and 2,8% having low knowledge.